1997
DOI: 10.1117/12.275745
|View full text |Cite
|
Sign up to set email alerts
|

<title>Crack detection on a full-scale aircraft fatigue test</title>

Abstract: This paper will present the findings from crack detection monitoring on the 777 full-scale aircraft during fatigue testing. Crack detection is a critical component of any comprehensive aircraft structural health-monitoring system. Health monitoring offers the promise of substantially reduced inspection and maintenance costs for military aircraft. To date, most testing has been performed in the laboratory on relatively small coupons and subcomponents. A persistent concern with broadband acoustic emission method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Early Boeing internal work demonstrated that Broadband Acoustic Emission (BAE) systems had the capability to detect crack growth in structure. 3 A BAE system can autonomously monitor aircraft structure during operation and provide information necessary to detect crack growth, determine the source location and monitor the crack growth without structural disassembly.…”
Section: Military Aircraft Applicationsmentioning
confidence: 99%
“…Early Boeing internal work demonstrated that Broadband Acoustic Emission (BAE) systems had the capability to detect crack growth in structure. 3 A BAE system can autonomously monitor aircraft structure during operation and provide information necessary to detect crack growth, determine the source location and monitor the crack growth without structural disassembly.…”
Section: Military Aircraft Applicationsmentioning
confidence: 99%
“…A resonant ultrasound spectroscopy apparatus was provided for detecting crack-like flaws in components in [2]. Searle et al applied an aircraft structural health-monitoring system to detect damaged areas in a full-scale aircraft fatigue tests [3]. Kadam et al [4] used a self-diagnosis technique to detect the cracking and de-bonding of the permanently embedded lead zirconate titanate (PZT).…”
Section: Introductionmentioning
confidence: 99%